PELATIHAN PENGEMBANGAN INOVASI MEDIA PEMBELAJARAN ”SCOEP” UNTUK MENINGKATKAN PENGUCAPAN BAHASA INGGRIS SISWA SMK - Kristanto, Barlian; Putri, Diannike; Krisbiantoro, Benny (Jurnal Abdi Insani, 2025)
The community service presents the results of training in the development of the innovative learning media "SCoEP" (Smart Card of English Pronunciation) based on the mnemonic method to improve the English pronunciation skills of Vocational High School (SMK) students. Through a series of stages, ranging from needs analysis, media design, development training, to implementation and evaluation, the "SCoEP" learning media was successfully developed and implemented at SMKN 1 Purwokerto. The results of the training show that the training in developing the "SCoEP" media is effective in improving the English pronunciation skills of SMK students. This is indicated by an increase in the average score from the pre-test to the post-test by 27.38%. The "SCoEP" learning media, which integrates visual elements, phonetic transcripts, and technology through QR codes, has been proven to help students remember vocabulary pronunciation more easily. This training also fostered enthusiasm and student participation in the learning process. These findings imply that the "SCoEP" learning media can be an effective and innovative solution to improve English pronunciation skills in Vocational High Schools. This media can be a development model that can be applied more widely to improve the quality of English language learning in SMK schools.